Health system reform in the Czech Republic. Policy lessons from the initial experience of the general health insurance company - Massaro, T A; Nemec, J; Kalman, I (JAMA, 1994)
The Czech Republic is among the most aggressive of the former Warsaw Pact countries in encouraging competition and free-market reform. This aggressiveness was extended into the health care sector when, in 1992, a mandatory employment-based health insurance system was introduced. The move from a controlled socialist structure to an insurance-based, fee-for-service model occurred in a short time. Health care spending increased 50% in 2 years and now approaches that of many industrialized nations. Claims for reimbursements are increasing at a rate of 5% to 7% per quarter. Market incentives have changed behaviors within the medical community. Newly privatized physicians generate greater volume and consume more resources than those continuing as state employees. Policy issues requiring further evaluation include supply, distribution, and relative valuation of physician services; clinical resource allocation; and cost containment.
Keywords: reforma zdravotní péče; dostupnost zdravotnických služeb; dávkové mechanismy; programy národního zdraví; Health Care Reform; Health Services Accessibility; Česká republika; Health Benefit Plans, Employee; National Health Programs; Reimbursement Mechanisms; Delivery of Health Care; nemocenské dávky pracujícím - plány; poskytování zdravotní péče; Czech Republic